Discourse on the Domestication of Women: The Role of the Family During the COVID-19 Pandemic in Mamah Dede's Lectures (A Study of Critical Discourse Analysis) - Zahra Munir, Hazalia; Anwar, Miftahulkhairah; Leiliyanti, Eva (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aimed to analyze the linguistic patterns employed by Mamah Dedeh in her lectures pertaining to the domestication of women, with a focus on assessing the language utilized. Two lectures were delivered by Mamah Dedeh, with each preaching having a duration of 4 minutes and 24 seconds and 3 minutes and 15 seconds, respectively. These lectures were recorded utilizing the stratified intentional sampling method amidst the COVID-19 pandemic. The analysis of the data involved the utilization of Halliday's transitivity theory and Martin and White's language evaluation theory, with the data presented in the form of transcripts of the two video lectures. The study revealed that Preaching I predominantly employed material and verbal mechanisms to communicate a message urging spouses to actively engage in domestic tasks. Consequently, as demonstrated by the second lecturer, it was established that the wife can contribute to the household's financial stability through employment.